Community structure and comparative analysis of the woody component of a cerrado remnant in Southeastern Brazil - Ishara, Katia Losano [UNESP]; Maimoni-Rodella, Rita de Cassia Sindrônia [UNESP] (Instituto de Botânica, 2010)
O presente estudo teve como objetivo realizar um levantamento florístico-estrutural da comunidade arbustivo-arbórea de um fragmento de cerrado sensu stricto no Estado de São Paulo e compará-lo com outras áreas de cerrado. Foram delimitadas 21 parcelas de 250 m² cada onde as plantas com diâmetro basal do caule igual ou superior a 3 cm foram incluídas na amostragem. Foram registrados 3062 indivíduos pertencentes a 58 espécies e 34 famílias. Asteraceae apresentou o maior número de espécies (sete), seguida por Fabaceae e Myrtaceae (cinco cada). As espécies mais importantes foram Tibouchina stenocarpa e Anadenanthera falcata. A composição florística da área de estudo indica que esta pode ser considerada como uma transição entre cerrado e floresta estacional semidecídua. A comparação com outras áreas indicou que há considerável heterogeneidade florístico-estrutural nas áreas de cerrado e as análises multivariadas mostraram que as áreas comparadas se agruparam de acordo com sua posição geográfica e tipo de solo.

The aims of the present work were to carry out a floristic-structural study of the shrubby-arboreal component of a savanna fragment (cerrado sensu stricto) in São Paulo State, Southeastern Brazil, and to compare with other areas. Twenty one plots of 250 m² each were delimited and plants with stem basal diameter equal or superior to 3 cm were included in the sampling. The recorded individuals corresponded to 3,062 and 58 species belonging to 34 families were registered. Asteraceae had the largest number of species (seven), followed by Fabaceae and Myrtaceae (five each). The most important species were Tibouchina stenocarpa and Anadenanthera falcata. The floristic composition of the study area indicates that it might be considered a transition from cerrado to seasonal semi-deciduous forest. The comparison with other surveys indicates floristic-structural heterogeneity of these cerrado areas and the multivariate analysis showed that areas grouped according to their geographical position and soil type.
Estrutura da comunidade e análises comparativas do componente lenhoso de um remanescente de cerrado na região Sudeste do Brasil
Keywords: fitossociologia; savana; similaridade; phytosociology; savanna; similarity